2013
DOI: 10.1093/jpepsy/jst093
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Monitoring of Medication Adherence in Early Maintenance Phase Treatment for Pediatric Leukemia and Lymphoma: Identifying Patterns of Nonadherence

Abstract: Adherence promotion interventions might be tailored to subgroups of patients who demonstrated problematic patterns of treatment adherence that could place them at risk for relapse. This research demonstrates the importance of using objective real-time measures of medication adherence for measuring and documenting adherence patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 25 publications
1
56
2
Order By: Relevance
“…In our study, the rate of nonadherence measured by the MMAS-8 for patients is higher than what has been reported previously. 8,[10][11][12]17 Hispanic and adolescent patients have higher rates of nonadherences. 10,46 The strength of our study is the diverse patient population, which is reflective of ALL patients treated at our center.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the rate of nonadherence measured by the MMAS-8 for patients is higher than what has been reported previously. 8,[10][11][12]17 Hispanic and adolescent patients have higher rates of nonadherences. 10,46 The strength of our study is the diverse patient population, which is reflective of ALL patients treated at our center.…”
Section: Discussionmentioning
confidence: 99%
“…1 Prior studies of adherence to oral 6MP in children with ALL have reported adherence rates ranging from 70% to 95% by using a variety of subjective and objective measures. [2][3][4][5][6][7][8][9] We have previously shown that inadequate systemic exposure to 6MP because of poor 6MP adherence (,95% adherence rate, objectively measured by the Medication Event Monitoring System [MEMS; WestRock Healthcare, Sion, Switzerland]) is associated with increased risk of relapse. 2,10 Accurate assessment of 6MP intake is therefore critical to ensure timely interventions for patients with poor adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mediation adherence should be assessed and monitored routinely throughout the course of treatment. For children and adolescents with leukemia or lymphoma who are prescribed two doses of 6MP per day, adherence decreases as rapidly as 6% per day, with rates falling as much as 40% over time . As children enter adolescence, the variability in the timing of medication administration often increases and nonadherence becomes even more prevalent .…”
Section: Discussionmentioning
confidence: 99%
“…For children and adolescents with leukemia or lymphoma who are prescribed two doses of 6MP per day, adherence decreases as rapidly as 6% per day, with rates falling as much as 40% over time . As children enter adolescence, the variability in the timing of medication administration often increases and nonadherence becomes even more prevalent . To capture the anticipated changes in medication adherence over time, providers are encouraged to assess and monitor medication adherence at each follow‐up outpatient clinic visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation